S1 Sacrectomy for Re-recurrent Rectal Cancer: Our Experience with Reconstruction Using an Expandable Vertebral Body Replacement Device. Issue 2 (February 2018) - Lee, Daniel Jin Keat; Wang, Kelvin Yafan; Sagar, Peter Michael; Timothy, Jake
Abstract : INTRODUCTION: R0 resection is achieved by high sacrectomy for local recurrence of colorectal cancer, but significant rates of perioperative complications and long-term patient morbidity are associated with this procedure. In this report, we outline our unique experience of using an expandable cage for vertebral body reconstruction following S1 sacrectomy in a 66-year-old patient with re-recurrent rectal cancer. We aim to highlight several key steps, with a view to improving postoperative outcomes. TECHNIQUE: A midline laparotomy was performed with the patient in supine Lloyd-Davies position, demonstrating recurrence of tumor at the S1 vertebral body. Subtotal vertebral body excision of S1 with sparing of the posterior wall and ventral foramina was completed by using an ultrasonic bone aspirator. Reconstruction was performed using an expandable corpectomy spacer system. The system was assembled and expanded in situ to optimally bridge the corpectomy. The device was secured into the L5 and S2 vertebrae by means of angled end plate screws superiorly and inferiorly. Bone grafts were positioned adjacent to the implant after this. RESULTS: Total operating time was 266 minutes with 350 mL of intraoperative blood loss. There were no immediate postoperative complications. The patient did not report any back pain at the time of discharge, and no neurological deficit was reported or identified. Postoperative CT scan showed excellent vertebral alignment and preservation of S1 height. CONCLUSION: We conclude that high sacrectomy with an expandable metal cage is feasible in the context of re-recurrent rectal cancer when consideration is given to the method of osteotomy and vertebral body replacement.